EL DICCIONARIO COMO MATERIAL DE REFERENCIA MÚLTIPLE PARA EL APRENDIZAJE DEL INGLÉS COMO L2 - Díaz Vidal, Jesús; Rodríguez Romero, Luis Fernando; Velázquez Ahumada, María Irene (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract This paper analyzes the different types of information that first and second year students of English Language and Literature look up in their dictionaries to facilitate their reading tasks. It does so in a twofold manner, first, by checking their preferences in terms of dictionary-type, and, second, by taking a closer look at the phonetic aspect of their search. The subjects were presented with a short text and were required to work on it with no time limit. They had at their disposal a number of dictionaries including monolingual, bilingual, slang, pronunciation and other varieties. Once they had finished, they were asked several questions concerning the use of the material at hand with respect to the linguistic components of lexis, semantics and phonology.